APRIORI ALGORITHM TESTING USING THE RAPIDMINER APPLICATION - Paska Marto Hasugian; Pandi Barita Nauli Simangunsung (Jurnal Info Sains : Informatika dan Sains, 2023)
In this study, the Apriori algorithm was tested using the RapidMiner application. Apriori algorithm is one of the algorithms used in association analysis in data mining. The purpose of this research is to test the performance of Apriori algorithm in identifying association patterns in the given dataset. The research method used is experimentation using relevant datasets. Testing is done by implementing the Apriori algorithm in the RapidMiner application, which provides a visual interface and various functions for data analysis. During testing, adjustments were made to Apriori algorithm parameters, such as support and confidence, to optimize analysis results. The data generated from the tests were evaluated to determine significant association patterns. The test results show the success rate of the Apriori algorithm in identifying association patterns in the given dataset. The performance evaluation of the algorithm is done based on relevant metrics, such as accuracy, execution speed, and association pattern quality score. The conclusion of this research is that testing the Apriori algorithm using the RapidMiner application can provide adequate results in association analysis. This research has important implications in the field of data mining and association analysis, especially in the use of the Apriori algorithm using the RapidMiner application. It is hoped that this research can contribute to the development of association analysis techniques and improve understanding of the performance of the Apriori algorithm in the context of its use in practical applications.